2018
DOI: 10.1002/anie.201809469
|View full text |Cite
|
Sign up to set email alerts
|

Camouflaging Structural Diversity: Co‐crystallization of Two Different Nanoparticles Having Different Cores But the Same Shell

Abstract: Two ligand‐protected nanoscale silver moieties, [Ag46(SPhMe2)24(PPh3)8](NO3)2 and [Ag40(SPhMe2)24(PPh3)8](NO3)2 (abbreviated as Ag46 and Ag40, respectively) with almost the same shell but different cores were synthesized simultaneously. As their external structures are identical, the clusters were not distinguishable and become co‐crystallized. The occupancy of each cluster was 50 %. The outer shell of both is composed of Ag32S24P8, which is reminiscent of fullerenes, and it encapsulates a well‐studied core, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 33 publications
0
92
0
Order By: Relevance
“…From top left to bottom right: Chiral phosphine/thiolate coprotected Ag and Ag-based bimetallic NCs: [Ag 15 (TP) 4 Cl 4 ] 3+ , [239] Ag 16 (SR) 14 (DPPE) 4 , [238] Ag 23 (SR) 18 (PPh 3 ) 8 , [240] [Au 1 Ag 24 (SR) 17 (DPPM) 3 ] 2+ , [241] Pt 1 Ag 28 (SR) 18 (PPh 3 ) 4 , [242] Ag 29 (SR) 12 (PPh 3 ) 4 , [221] [Ag 32 (SR) 24 (DPPE) 5 ] 2− , [238] [Ag 32 (SR) 13 (DPPM) 5 Cl 8 ] 3+ , [243] Ag 33 (SR) 24 (PPh 3 ) 4 , [244] Ag 43 (SR) 25 (PPh 3 ) 4 , [245] [Ag 45 (SR) 16 (DPPM) 4 Br 12 ] 3+ , [243] Au 9 Ag 36 -(SR) 27 (PPh 3 ) 6 , [246] [Ag 67 (SR) 32 (PPh 3 ) 8 ] 3+ , [247] Ag 78 (SR) 42 (DPPP) 6 . [248] Achiral phosphine/thiolate coprotected Ag NCs: Ag 14 (SR) 12 -(PPh 3 ) 8 , [249] Pt 1 Ag 26 (SR) 18 (PPh 3 ) 6 , [250] Ag 38 (SR) 26 (PPh 3 ) 8 , [251] Ag 46 (SR) 24 (PPh 3 ) 8 , [245,252] Ag 50 (SR) 30 (DPPM) 6 , [253] Ag 63 (SR) 36 (PPh 3 ) 8 . [251] As shown in Scheme 5, as the involvement of phosphine in Ag NCs does not change the surface bonding, i.e., the S coordination in the outmost Ag-S-P cage is not affected, it is still the distortion of the Ag-S-P mount motifs or the Ag-S-P cages that decides the chirality of the clusters.…”
Section: Thiolate/phosphine Coprotected Ag Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…From top left to bottom right: Chiral phosphine/thiolate coprotected Ag and Ag-based bimetallic NCs: [Ag 15 (TP) 4 Cl 4 ] 3+ , [239] Ag 16 (SR) 14 (DPPE) 4 , [238] Ag 23 (SR) 18 (PPh 3 ) 8 , [240] [Au 1 Ag 24 (SR) 17 (DPPM) 3 ] 2+ , [241] Pt 1 Ag 28 (SR) 18 (PPh 3 ) 4 , [242] Ag 29 (SR) 12 (PPh 3 ) 4 , [221] [Ag 32 (SR) 24 (DPPE) 5 ] 2− , [238] [Ag 32 (SR) 13 (DPPM) 5 Cl 8 ] 3+ , [243] Ag 33 (SR) 24 (PPh 3 ) 4 , [244] Ag 43 (SR) 25 (PPh 3 ) 4 , [245] [Ag 45 (SR) 16 (DPPM) 4 Br 12 ] 3+ , [243] Au 9 Ag 36 -(SR) 27 (PPh 3 ) 6 , [246] [Ag 67 (SR) 32 (PPh 3 ) 8 ] 3+ , [247] Ag 78 (SR) 42 (DPPP) 6 . [248] Achiral phosphine/thiolate coprotected Ag NCs: Ag 14 (SR) 12 -(PPh 3 ) 8 , [249] Pt 1 Ag 26 (SR) 18 (PPh 3 ) 6 , [250] Ag 38 (SR) 26 (PPh 3 ) 8 , [251] Ag 46 (SR) 24 (PPh 3 ) 8 , [245,252] Ag 50 (SR) 30 (DPPM) 6 , [253] Ag 63 (SR) 36 (PPh 3 ) 8 . [251] As shown in Scheme 5, as the involvement of phosphine in Ag NCs does not change the surface bonding, i.e., the S coordination in the outmost Ag-S-P cage is not affected, it is still the distortion of the Ag-S-P mount motifs or the Ag-S-P cages that decides the chirality of the clusters.…”
Section: Thiolate/phosphine Coprotected Ag Ncsmentioning
confidence: 99%
“…Achiral phosphine/thiolate coprotected Ag NCs: Ag 14 (SR) 12 (PPh 3 ) 8 ,249 Pt 1 Ag 26 (SR) 18 (PPh 3 ) 6 ,250 Ag 38 (SR) 26 (PPh 3 ) 8 ,251 Ag 46 (SR) 24 (PPh 3 ) 8 ,245,252 Ag 50 (SR) 30 (DPPM) 6 ,253 Ag 63 (SR) 36 (PPh 3 ) 8 251…”
Section: Beyond the Au‐sr Nanoclustersmentioning
confidence: 99%
“…[ 5–8 ] Therefore, nanocluster can be represented by formulas as [M n (L) m ] q (n, m, and q denote the number of metal atoms, ligands, and charges in the nanocluster, respectively), just like the molecular compound. [ 9–20 ] Furthermore, the free electrons in nanoclusters can significantly influence their physical–chemical properties. [ 21 ] In addition, the precise compositions and well‐defined sizes of nanoclusters are also helpful for understanding the structure–property relationships which are necessary for rationally designing the nanoclusters with enhanced performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports on atomically precise NCs have shed light on some interesting phenomena. For example, Bakr,P radeep and our group recently reported that [Ag 67 S 32 P 8 ] 3 + (Ag 67 ) [35] and [Ag 46 S 24 P 8 ] 2 + (Ag 46 ) [36,37] adopt the FCC space group and bear eight corner phosphine ligands, similarly to the aforementioned Ag 14 , Ag 23 , Ag 38 ,a nd Ag 63 NCs. [31][32][33][34] However, Ag 67 and Ag 46 are exceptionstot he 1D/2D/3D evolution formula, due to their half-cubic [32] growth (Figure 1b vs. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] The atomic precision with which the structures of these "clustero fc lusters" is understood has allowed the deduction of structure-property correlations. For example, the lowest-energya bsorption peak of Au 13 ,A u 25 ,a nd the rod-likeA u 37 has been found to continuously redshiftw ith increasing size of the NCs. [19] Similarly,f or the aforementioned Au 28 ,A u 36 ,A u 44 ,a nd Au 52 ,t he UV/Vis spectra indicate ad ecreased HOMO-LUMO gap, [22] and femtosecond pump/nanosecond probet ransienta bsorption spectroscopy shows ab roadening of the excited-state absorption with increasingn anocluster size.…”
Section: Introductionmentioning
confidence: 92%